Dependência da resposta não linear de nanotubos de carbono de parede única com a singularidade de Van Hove - Aréstegui Sierra, Odón (2017)
In the present work, we have studied the nonlinear optical properties of purely electronic origin in colloidal samples containing semiconductor single wall carbon nanotubes (s-SWCNTs) of different chiralities prepared under two methods, synthesis by cobalt–molybdenum catalyst (CoMoCAT) separated using column chromatography and synthesis by High-Pressure decomposition of Carbon monoxide (HiPCO) with Aqueous Two-Phase Extraction (ATPE). For nonlinear measurementswas assembled the Z-scanning technique with high repetition rate laser modulated by a chopper.All samples (SW01, SW02 and SW6,5) showed a 2 (n <0) negative nonlinear refractive index behavior, the dispersion curves | 2 | n generated due to the Z-scan with laser wavelengths in resonance with the nanotubes absorption band show a similar behavior with the linear absorption band, effect due to one-photon absorption processes. For SW01 can be seen the nonlinear absorption behavior (β) saturated (SA) and reverse saturated (RSA), however, in the other samples SW02 and SW6,5 did not show nonlinear absorption due to low sensitivity of the Z-scan system. The analysis and fulfillment of the figures of merit indicate that these s-SWCNTS are promising materials for applications in ultrafast optical switching devices.